Banks’ intraday liquidity management during operational outages: Theory and evidence from the UK payment system - Merrouche, Ouarda; Schanz, Jochen (Journal of Banking & Finance, 2010)
We investigate how settlement banks in the United Kingdom’s large-value payment system deal with intraday liquidity and operational risk. In particular, we are interested in payments behaviour towards a bank that is, for operational reasons, unable to make but able to receive payments. If other banks did not sufficiently monitor their outgoing payments, these operational shocks could impact the entire payment system because the affected bank could absorb liquidity from the system. Our game-theoretic model predicts that only early in the day, when they are uncertain about the payment instructions they might have to execute, banks stop sending payments to a counterparty which is unable to make payments. Using a non-parametric method, we find that this prediction is supported by the data, implying that banks effectively contain the disruption caused by the operational outage: payment flows between healthy banks remain unaffected.